THE EFFECT OF A JIGSAW-TYPE COOPERATIVE LEARNING MODEL BASED ON BLENDED LEARNING USING GOOGLE CLASSROOM HAS AN IMPACT ON STUDENT LEARNING OUTCOMES ON VECTOR MATERIAL - Sipahutar, Nur Halimah (Universitas Negeri Medan, 2023)
This study aims to determine the effect of the jigsaw cooperative learning model based on blended learning by utilizing google classroom on student learning outcomes in vector material. This study used a quasi-experimental type of research. The data collection method used was test instruments (pretest and posttest) which were distributed to two classes, namely class X Mipa 3 as the control class and class X Mipa 2 as the experimental class. The test instrument used was 15 questions in the form of multiple choice which had been tested for validity, discriminatory power, level of difficulty, and reliability. The population in this study were all students of class X MAN 2 North Labuhanbatu as many as 6 classes. The average number of students in each class is 36 people. Two classes of samples were selected using simple random sampling technique. Based on the results of the calculation of the hypothesis test using the one-party t test at a significance level of 5% and dk = 36, a tcount value of 3.27 is obtained and a ttable value is 1.99 or tcount > ttable, so that it can be stated that Ha is accepted and H0 is rejected. So it can be concluded that the application of the jigsaw type cooperative learning model based on blended learning by utilizing google classroom has an effect on student learning outcomes in vector material.